2003
DOI: 10.1194/jlr.r300002-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Familial hypobetalipoproteinemia: a review

Abstract: We review the genetics and pathophysiology of familial hypobetalipoproteinemia (FHBL), a mildly symptomatic genetically heterogeneous autosomal trait. The minority of human FHBL is caused by truncation-specifying mutations of the APOB gene on chromosome 2. In seven families, linkage to chromosome 2 is absent, linkage is instead to chromosome 3 (3p21). In others, linkage is absent to both APOB and to 3p21. Apolipoprotein B-100 (apoB-100) levels are ‫ف‬ 25% of normal, instead of the 50% expected based on the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
108
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(112 citation statements)
references
References 64 publications
0
108
1
Order By: Relevance
“…14 Familial hypobetalipoproteinemia (FHBL) (OMIM 107730) is a codominant disorder of lipoprotein metabolism characterized by low levels ( < 5th percentile for age and sex) of LDL-cholesterol and apoB. 15,16 Over 50 mutations in the APOB gene, on chromosome 2, have been described to date, which either affect splicing or result in the production of truncated apoB isoforms. 17 Immunoblotting is the primary means for detecting truncated apoB isoforms in plasma.…”
Section: Introductionmentioning
confidence: 99%
“…14 Familial hypobetalipoproteinemia (FHBL) (OMIM 107730) is a codominant disorder of lipoprotein metabolism characterized by low levels ( < 5th percentile for age and sex) of LDL-cholesterol and apoB. 15,16 Over 50 mutations in the APOB gene, on chromosome 2, have been described to date, which either affect splicing or result in the production of truncated apoB isoforms. 17 Immunoblotting is the primary means for detecting truncated apoB isoforms in plasma.…”
Section: Introductionmentioning
confidence: 99%
“…VLDL synthesis is initiated in the endoplasmic reticulum (ER) of hepatocytes following the synthesis of the apolipoprotein (Apo) B100 and recruitment of TGs, cholesterol esters, and other apolipoproteins such as ApoE. ApoB mutations affect plasma lipid levels and are associated with familial hypobetalipoproteinemia disease [8]. Although more and more genes have been found to be involved in lipoprotein assembly and transport, and their disruption is associated with hepatic steatosis, the underlying mechanisms are still not very clear [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Heterozygotes are usually asymptomatic with LDL cholesterol and apoB-100 concentrations Ͻ50% of those in normal plasma. Homozygotes have undetectable plasma LDL cholesterol and apoB, and their clinical presentation, depending on the specific mutation, varies from no symptoms to severe gastrointestinal and neurological dysfunction, similar to that in abetalipoproteinemia (27,28,30). Nonsense, frameshift, and splicing mutations in the APOB gene leading to formation of prematurely truncated apoB species have been reported in FHBL subjects (27)(28)(29)(30).…”
mentioning
confidence: 99%
“…Familial hypobetalipoproteinemia (FHBL; OMIM 107730) is a genetically heterogeneous autosomal co-dominant disorder characterized by low levels (Ͻ5th percentile for age and sex) of plasma apoB-containing lipoproteins (27)(28)(29)(30). It has been suggested that FHBL represents a longevity syndrome (31) and might be associated with cardiovascular protection because of resistance to atherosclerosis (32).…”
mentioning
confidence: 99%